Modeling the impact of information technology governance effectiveness using partial least square - Kaur, Jasber; Mohamed, Norshidah; Ahlan, Abdul Rahman (2012)
The practice of information technology (IT)governance entails activities that ensures stakeholder needs are evaluated to determine balanced, agreed upon enterprise objectives to be achieved; setting direction through IT-related prioritisation and decision making, and monitoring performance and compliance against agreed upon direction and objectives. Thus, the purpose of this paper is to analyze the impact of IT governance effectiveness in private sector organizations in a developing country such as Malaysia. Based on extant literature review, a research model was developed for analyzing the relationship between the practices for effective IT governance in this environment and their effect on organizational performance. A survey research method was applied for data collection and sample data from Malaysian private sector organizations (this environment) obtained. Subsequently, structural equation modeling technique, namely partial least squares, was applied to test statistically the correlated effects. The results indicate significant small to strong positive correlated effects on IT governance effectiveness. Finally, a model for effective IT governance in this environment was proposed. The findings imply that decision makers can optimize IT-related plans and use of scarce resources by concentrating on the factors that have a significant effect on organizational performance that could lead to an improvement of service delivery.